2013
DOI: 10.1186/2036-7902-5-s1-s2
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of ultrasonography in the diagnosis of acute appendicitis in adult patients: review of the literature

Abstract: BackgroundUltrasound is a widely used technique in the diagnosis of acute appendicitis; nevertheless, its utilization still remains controversial.MethodsThe accuracy of the Ultrasound technique in the diagnosis of acute appendicitis in the adult patient, as shown in the literature, was searched for.ResultsThe gold standard for the diagnosis of appendicitis still remains pathologic confirmation after appendectomy. In the published literature, graded-compression Ultrasound has shown an extremely variable diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 20 publications
6
53
1
4
Order By: Relevance
“…The overall sensitivity, specificity and PPV of US in adult and adolescent patients in various published series have been 86%, 81% and 84% respectively. 8 In our study conducted over a 22-month period, we found US to be reliable when positive for appendicitis, as the PPV was 89.5% and the NAR after operation was 10.5%. This may be attributed to better training of radiologists, as well as the recent improvements in ultrasonography imaging techniques and newer US machines.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The overall sensitivity, specificity and PPV of US in adult and adolescent patients in various published series have been 86%, 81% and 84% respectively. 8 In our study conducted over a 22-month period, we found US to be reliable when positive for appendicitis, as the PPV was 89.5% and the NAR after operation was 10.5%. This may be attributed to better training of radiologists, as well as the recent improvements in ultrasonography imaging techniques and newer US machines.…”
Section: Discussionmentioning
confidence: 58%
“…However, ultrasonography is highly operator dependent with a consequently wide reported sensitivity range (44% -100%). 8 Advantages of CT include less operator dependence, easier visualization of retrocaecal appendix, less interference of bowel gas, obesity or patient's pain and tenderness with good image quality. A major disadvantage of CT is the radiation exposure which is the major caveat and the single most important consideration in avoidance of the examination.⁶ Secondly cost is an impediment for the average Indian patient.…”
Section: Introductionmentioning
confidence: 99%
“…This is while the diagnostic accuracy of radiologist performed ultrasound study in diagnosis of acute appendicitis still remains conflicting and indistinct, and different studies show different results. As Terasawa et al showed in their review on 14 studies that ultrasonography has a sensitivity of 86 %, specificity of 81 %, positive predictive value of 84 % and a negative predictive value of 85 % in diagnosing acute appendicitis in patients with right lower quadrant pain and suspicious to have acute appendicitis [7], a large meta-analysis (including 22 articles) in Korea found also a sensitivity of 87 % and specificity of 90 % for sonography in acute appendicitis and another review by Pinto et al showed also the acceptable overall accuracy for ultrasound study in diagnosis of acute appendicitis [8]. But there are other studies showing positive predictive value ranging from 46 to 95 % and the negative predictive value ranging from 60 to 97 % for this diagnostic imaging modality [9][10][11][12][13].…”
Section: Discussionmentioning
confidence: 98%
“…The diagnosis of acute uncomplicated appendicitis with fewer than 48 hours of symptoms was made according to history, physical examination result, WBC count, and ultrasonographic findings showing evidence of non-ruptured appendicitis with an appendiceal diameter of 1.1 cm or less [13]. Exclusion criteria included suspicion of perforation, appendiceal mass, symptoms lasting more than 48 hours or previous non-operative treatment of acute appendicitis.…”
Section: Methodsmentioning
confidence: 99%